2010
DOI: 10.1007/s11940-009-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Headache

Abstract: Headache has been linked to a wide range of sleep disorders that may impact headache management. There are no evidence-based guidelines, but the authors believe that literature supports the following clinical recommendations: 1. Diagnose headache according to standardized criteria. Specific diagnoses are associated with increased risk for specific sleep and psychiatric disorders. 2. Collect sleep history in relation to headache patterns. Screening questionnaires and prediction equations are cost-effective. 3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 48 publications
2
18
0
1
Order By: Relevance
“…There are also evidences that rapid eye movement (REM) sleep deprivation is especially linked to hyperalgesia [45]. A significant association between severe sleep disturbances and chronic headache [46, 47] and central sensitization [48] has further been reported. Poor quality of sleep promotes diffusion of myofascial pain in headache patients, but which sleep phase is more involved in the generation of widespread pain remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…There are also evidences that rapid eye movement (REM) sleep deprivation is especially linked to hyperalgesia [45]. A significant association between severe sleep disturbances and chronic headache [46, 47] and central sensitization [48] has further been reported. Poor quality of sleep promotes diffusion of myofascial pain in headache patients, but which sleep phase is more involved in the generation of widespread pain remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…A review of population-based longitudinal and cross-sectional studies showed that these types of headache are significantly related to insomnia symptoms, especially when frequent or severe, and some studies have also demonstrated bidirectional causality [74]. Virtually all sleep disorders, particularly OSA, are more prevalent among headache patients compared to HC, and dysregulation of sleep is a frequent trigger of migraine and TTH [75]. …”
Section: Migraine and Tension-type Headachementioning
confidence: 99%
“…Clinical and preclinical data concur that sleep disruption causes hyperalgesia, and despite the widely distributed and overlapping neural networks that regulate states of sleep and pain, the brain mechanisms through which sleep and pain interact remain poorly understood [40,41]. A significant association of severe sleep disturbances and chronic headache [42,43] with central sensitization [44] has also been reported. Poor quality of sleep promotes diffusion of myofascial pain in headache patients, but which sleep phase is more involved in the generation of widespread pain remains to be clarified.…”
mentioning
confidence: 99%